A mobile core-body temperature monitoring system on android - Pereira, Orlando R. E. (2013)
Recently, Google launched the Android mobile operating system and several mobile devices already support it. This paper proposes a mobile Android-enabled tool for collecting, monitoring, and analyzing intra-vaginal temperature. A previous proposed intra-vaginal sensor acquires temperature values and sends the collected data to Android device over a Bluetooth connection. The Android tool allows women for real-time monitoring of their temperature with mobility support and following their daily life. Woman can control and detect their fertile and ovulation periods when this human parameter increases about 0.5ºC over their regular temperature. Other application of this solution includes the preterm labor prevention. The proposed system was evaluated and validated, and it is ready for use.